Replication fork collapse at a protein‐DNA roadblock leads to fork reversal, promoted by the RecQ helicase. Issue 2 (9th December 2018) - Weaver, Georgia M.; Mettrick, Karla A.; Corocher, Tayla‐Ann; Graham, Adam; Grainge, Ian
Summary: Proteins that bind DNA are the cause of the majority of impediments to replication fork progression and can lead to subsequent collapse of the replication fork. Failure to deal with fork collapse efficiently leads to mutation or cell death. Several models have been proposed for how a cell processes a stalled or collapsed replication fork; eukaryotes and bacteria are not dissimilar in terms of the general pathways undertaken to deal with these events. This study shows that replication fork regression, the combination of replication fork reversal leading to formation of a Holliday Junction along with exonuclease digestion, is the preferred pathway for dealing with a collapsed fork in Escherichia coli. Direct endo‐nuclease activity at the replication fork was not observed. The protein that had the greatest effect on these fork processing events was the RecQ helicase, while RecG and RuvABC, which have previously been implicated in this process, were found to play a lesser role. Eukaryotic RecQ homologues, BLM and WRN, have also been implicated in processing events following replication fork collapse and may reflect a conserved mechanism. Finally, the SOS response was not induced by the protein‐DNA roadblock under these conditions, so did not affect fork processing. Abstract : DNA replication can be halted at any of the many proteins that coat DNA inside a cell. If the replisome copying the DNA dissociates, then the RecQ helicase plays a key role in processing this DNA to avoid mutation or death.